Impact of defect migration on electrical and dielectric properties in molten salt synthesized CaCu3Ti4O12 and customizing the properties by compositional engineering with Mg doping - Yadav B.; Kar K.K.; Ghorai M.K.; Kumar D.; Yadav D. (My University, 2025)
For the CaCu3Ti4O12 (CCTO) synthesized using the molten salt method, sintered at 973–1273 K, the effect of extrinsic and intrinsic point defects on conductivity and dielectric behavior in the temperature range 300–450 K and frequency range 20 Hz–1 MHz was studied. The crystal structure, microstructures, and ionic distribution were studied by XRD, SEM, and EDS. The energy-dispersive X-ray spectroscopy, EDS, revealed qualitatively that CCTO has a minor deficiency of O and Ca and a slight excess of Ti and Cu. To maintain electrical neutrality, this results in the formation of V●●O, e/, h●, Ti3+, and Cu1+, etc., as complimentary point defects leading to an increased loss. Dielectric loss (tan δ ∼ 6–7 at ∼300 K/20 Hz) in a low-temperature regime was observed due to extrinsic defects migration with activation energy. EaσdcMott's ∼0.028 eV through Mott's variable range hopping. For temperatures ≥350 K, long-range conduction occurs due to an avalanche of intrinsic defects accumulated at sample electrode interface having activation energy, EaArrhenius's ∼0.177 eV, culminating in loss, tanδ ∼40 at ∼450 K/20 Hz). To minimize excessive loss, compositional engineering was done in CCTO by substituting Mg at the Ti site. Judicious choice of Mg doping, having high Schottky defect formation energy (ΔHf ≈ 7.7 eV) at Ti site (CCTMgO) resulted in almost temperature-independent dielectric constant, εr ≈ 103 and a significant reduction in the loss at ∼ 300–370 K in the frequency range 20 Hz - 1 kHz. Phase formation, structural refinements, etc., were further investigated in CCTMgO using the Rietveld refinement technique. © 2022 Elsevier B.V.